Trump Revealed : The Definitive Biography of the 45th President - Kranish, Michael and Fisher, Marc (London Simon & Schuster, 2017)
"Who is Donald J. Trump? To discover Trump in full, the Washington Post assembled a team of award-winning reporters and researchers to investigate every aspect of his life, from his privileged upbringing in Queens to his hundreds of lawsuits, his infamous womanizing, his shifting position on abortion rights, his dizzying seven changes in party affiliation, and his astonishing, disruptive election as president in November 2016"--Page 4 of cover.
Include Notes and Index
Keywords: Presidential candidates -- United States -- Presidents--Election